Using confidence intervals to compare several correlated areas under the receiver operating characteristic curves - Zou, G. Y.; Yue, Li (Statistics in medicine, 2013)
The performance of a diagnostic tool yielding quantitative or ordinal measurements is often assessed in terms of its area under the receiver operating characteristic curve (AUC). As new diagnostic tools are constantly being developed, a frequently occurring task is to compare multiple AUCs as derived from the same group of subjects. For this purpose, previous methods have usually used an omnibus chi‐square test, which may not be very informative. We present here methods for comparing several correlated AUCs using simultaneous confidence intervals. To improve small sample properties, we adopt the method of variance estimates recovery in which confidence limits for each AUC are obtained on the basis of the logit and inverse hyperbolic sine transformations. A simulation study demonstrates the superior performance of the proposed approach. The methods are illustrated with two examples. Copyright © 2013 John Wiley & Sons, Ltd.